Familial Analysis of Patients with Hypertension in Jatinangor, West Java, Indonesia - Keumala Hayati; Yulia Sofiatin; Sri Endah Rahayuningsih; Rully M.A. Roesli (Althea Medical Journal, 2017)
Background: Hypertension is a disease that is influenced by genetic factors, although the single gene affecting the occurrence of the disease has not been yet discovered. Genetic analysis and familial analysis on hypertension are needed to be done but genetic analysis needs substantial fund, and familial analysis on hypertension has been never done in community. Besides sharing the genetic factors, family also shares similar environment and life style. Latest study showed that the association between genetic and environmental factors can affect the phenotype of chronic disease suchas hypertension. The study was aimed to explore the family history contribution of patients with hypertension in Jatinangor.Methods: This was a descriptive-quantitave study. The subjects were 283 hypertensive patients in Jatinangor with complete data of family history. The data was retrospectively obtained from secondary data of a previous study conducted in Community Health and Well-ness Study Center, Faculty of Medicine, Universitas Padjadjaran titled Epidemiology of Hypertension and Albuminuria in Jatinangor 2014. Familial analysis conducted in this study was modified trios analysis.Results: In this modified trios analysis, there was only 20% of total patients with hypertension who have history of hypertension in two generations of their family. The proportion of patients with hypertension who have history of hypertension in one generation of their family was greater. More than 45% from the total 283 patients with hypertension analyzed in this study have family history of hypertension.Conclusions: Familial analysis using modified trios analysis showed similar results with the study conducted using other genetical analysis.